1999
DOI: 10.1073/pnas.96.14.7986
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of spermatogenesis in mice lacking a functional aromatase (cyp 19) gene

Abstract: It is well established that spermatogenesis is controlled by gonadotrophins and testosterone. However, a role for estrogens in male reproduction recently was suggested in adult mice deficient in estrogen receptor ␣. . Despite the demonstration of the aromatase enzyme, which converts androgens to estrogens, and estrogen receptors within the rodent seminiferous epithelium, the role of aromatase and estrogen in germ cell development is unknown. We have investigated spermatogenesis in mice that lack aromatase beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
360
5
15

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 564 publications
(405 citation statements)
references
References 40 publications
(49 reference statements)
22
360
5
15
Order By: Relevance
“…Many studies have underlined the importance of estrogens in male fertility [5,[32][33][34], as demonstrated by the expression of ERs and aromatase in the testis and by the fact that mice lacking either ERa [5] or aromatase [6] show altered spermatogenesis and infertility. However, evidence for a direct action of E 2 on the seminiferous epithelium is still missing, and remarkably genes that are regulated by E 2 through classical ERE sequences remain unknown in the testis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have underlined the importance of estrogens in male fertility [5,[32][33][34], as demonstrated by the expression of ERs and aromatase in the testis and by the fact that mice lacking either ERa [5] or aromatase [6] show altered spermatogenesis and infertility. However, evidence for a direct action of E 2 on the seminiferous epithelium is still missing, and remarkably genes that are regulated by E 2 through classical ERE sequences remain unknown in the testis.…”
Section: Discussionmentioning
confidence: 99%
“…Growing interest in the effects of E 2 in male reproduction is linked to the observation that ERs knockout [5] or disruption of E 2 synthesis [6] impair male fertility. Although some putative direct target genes of E 2 have been found in the testis [7][8][9], up to now the identification of a testicular cell-specific ER responsive promoter has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In knockout models, removing the ERα (αERKO) or the aromatase genes (ArKO) showed deficiency in the process of spermatogenesis and subsequently, reduced epididymal sperm count, sperm motility and fertilizing ability [99]. Recently, the genetic screening of the ERα gene locus has revealed the existence of several polymorphic sites including the PvuII (T397C) and XbaI restriction fragment length polymorphisms (RFLPs) in intron I and the (TA)n variable number of tandem repeats (VNTR) within the promoter region of the gene [21].…”
Section: The Estrogen Receptors (Esr) Genes Mutationsmentioning
confidence: 99%
“…Estradiol has recently been reported to play an important role in male reproductive health. Studies of estrogen receptor α (ERα) knockout and aromatase knockout mice first suggested an indirect role of estrogens in male fertility (3)(4)(5). Male ERα knockout mice were infertile, with post-pubertal degeneration of the testes and disrupted spermatogenesis (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Male ERα knockout mice were infertile, with post-pubertal degeneration of the testes and disrupted spermatogenesis (3,4). Estradiol is produced in the testes from aromatized testosterone, and progressive disruption of spermatogenesis and infertility was also observed among aromatase knockout mice (5). A direct role of estradiol as a germ cell survival factor was then demonstrated in the human testis in vitro, where estradiol was shown to inhibit testicular apoptosis much more effectively than testosterone (2).…”
Section: Introductionmentioning
confidence: 99%